Density Functional Theory Study of Pressure-Dependent Structural and Electronic Properties of Cubic Zirconium Dioxide - Zhussupbek M. Salikhodzha; Guldari B. Bairbayeva; Raigul N. Kassymkhanova; Marina Konuhova; Keleshek B. Zhangylyssov; Elena Popova; Anatoli I. Popov (Ceramics)
In this study, the structural, electronic, and elastic properties of cubic zirconium dioxide (c-ZrO2) were investigated using the Density Functional Theory (DFT) approach. Lattice parameter optimization revealed that the lattice constant is 5.107 Å, the Zr–O bond length is 2.21 Å, and the unit cell density is 6.075 g/cm3 for the B3LYP functional. The bandgap width was determined to be 5.1722 eV. The investigation of the elastic properties of the cubic ZrO2 crystal determined the Young’s modulus, bulk modulus, Poisson’s ratio, and hardness, which were found to be 315.91 GPa, 241 GPa, 0.282, and 13 (Hv), respectively, under zero external pressure. These results confirm the mechanical stability of ZrO2.